Desenvolvimento de rotina em linguagem matlab para processamento de dados de ondas geradas pelo vento - LIMA, Antônia pamela yhaohannah (2020)
The determination of the waves’ components as significant height, height maximum, significant period, length and depth is relevant to the characterization of the sea state since it gives the possibility of identifying their contribution to the wave climate of a particular region. The satellite images and the computational simulation are very used tools in the characterization of the parameters of a wave field; however, it depends on the data collection in situ to obtain a great level of data certainty. The samples in situ can be approached by oceanographic buoys, ondographos or by an equipment that has a pressure sensor, the last one is a good alternative to the elevate cost of the implementation of the buoys. However, pressure sensors, it does not presents programs or systems that can work with this procedure.The objective of the present study was to develop routines on MatLab language, focusing on the Amazon coastal area as an alternative methodology to the processing and analysis of this data. The data collection was done between the years 2011 and 2015 in 3 environments distributed throughout the Amazon coastal zone, which have different characteristics due to the degree of exposure of these to contact the ocean. The instruments equipped with pressure sensors were anchored and programmed to execute measurements on sample frequency of 0.1 and 0.5 s. Were developed two different functions, the first one processed the data entry obteined from the equipment and pre-treated, resulting in the parameters significant height, height maximum, significant period, length and depth, based on the Linear Theory of Airy, which is the second function. These functions were submitted to statistical tests to the comparison between the methods of collection and the results’ validation. The statistical tests portrayed that the waves’ registers obtained in thirty minutes of collection represent 95% of the data sampled in one hour of collection and that the data collected in each ten minutes represent 90% of the data in one hour. In addition, the average of the results obteined to the significance height and significant periods from the methods of the ascended zero and the descended zero were similar. The values of significant height and Significant wave period, are the same at those represented by the literature, thus validating the application of the developed routine for the treatment of waves on the Amazon region.